Alienation and Isolation: A Marxist Analysis in The Sea Speaks His Name by Leila S. Chudori - Izra Sesafya Tsabit; Ruly Indra Darmawan (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study examines the representation of alienation and isolation in The Sea Speaks His Name by Leila S. Chudori through a Marxist perspective. It focuses on how socio-political conditions during Indonesia’s New Order era shape the characters’ experiences of disconnection from the self and society. Using a qualitative, library-based approach, the research analyzes selected dialogues, monologues, and narrative elements in the novel. Drawing on Karl Marx’s concept of alienation, the findings indicate that the characters experience various forms of estrangement, particularly in relation to identity, social relations, and agency. These conditions are closely associated with state repression and authoritarian control, which contribute to both physical and psychological forms of isolation. However, the effects of alienation are not uniform, as the narrative also presents moments of awareness and relational connection. Overall, the study suggests that the novel portrays alienation as a complex condition shaped by structural forces while still allowing space for human agency. In this way, literature functions not only as a reflection of socio-political realities but also as a medium for exploring the tensions between domination and resistance.